Implementasi Metode Rapid Application Development pada Sistem Pencatatan Laporan Pick-Up dan Delivery Pakaian berbasis Android pada Hotel XYZ - Septiana, Via; winanti, winanti; Carolina, Yuanita; Nurasiah, Nurasiah; Suwita, Jaka (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
Laundry is one of the operational facilities in hotels. Hotel guests can use the laundry service to wash their clothes when staying at the hotel. One of the guests staying at the hotel is Airline Crew from various airlines. The current laundry system is not running well because there are still problems that occur, namely hotel guests sometimes do not completely fill out the list form in the hotel room, such as not filling in the room number and incompletely filling in the clothes to be laundered and the quantity. So the laundry staff has difficulty when delivering clean clothes because there is no room number information. In addition, there are complaints from guests because the number of clothes received does not match the number of clothes originally laundered. This research produces a laundry application created using the Flutter application and the MySQL Lite database. The system created consists of 4 users: guests, laundry, checkers, and supervisors. This research uses the PIECES analysis research method, RAD (Rapid Application Deployment) development and testing using blackbox testing